2019
DOI: 10.1097/ju.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Evaluation and Management Visits for Urinary Incontinence in Older Women

Abstract: Objective: The aim of this investigation was to examine how often outpatient visits addressing urinary incontinence among women with self-reported incontinence symptoms occur and to explore characteristics associated with having an outpatient visit for incontinence. Methods: We studied 18,576 women from the Nurses' Health Study, ages 65 years and older, who reported prevalent incontinence symptoms in 2012 on a mailed questionnaire and were linked with Medicare utilization data. We compared women with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…We next modeled different patient profiles based on age and body mass index to predict patterns of UI symptom progression among these groups (Table 3). Among women <60 years (N=7183) and women 70+ years (N=1696), the predicted probabilities of progressing from urgency to mixed UI were modest; for example, women less than 60 years old at UI onset with mild or moderate urgency UI had a 17% (95% CI: 17, 18) probability of mixed UI 8 years after onset; among women 70 years or older with mild or moderate urgency UI, this probability was 16% (95% CI: 16,17). On the other hand, women less than 60 years old with severe stress UI at onset had a 23% (95% CI: 23, 24) predicted probability of mixed UI 8 years later; for women 70 years or older, this probability was 33% (95% CI: 32-33).…”
Section: Resultsmentioning
confidence: 99%
“…We next modeled different patient profiles based on age and body mass index to predict patterns of UI symptom progression among these groups (Table 3). Among women <60 years (N=7183) and women 70+ years (N=1696), the predicted probabilities of progressing from urgency to mixed UI were modest; for example, women less than 60 years old at UI onset with mild or moderate urgency UI had a 17% (95% CI: 17, 18) probability of mixed UI 8 years after onset; among women 70 years or older with mild or moderate urgency UI, this probability was 16% (95% CI: 16,17). On the other hand, women less than 60 years old with severe stress UI at onset had a 23% (95% CI: 23, 24) predicted probability of mixed UI 8 years later; for women 70 years or older, this probability was 33% (95% CI: 32-33).…”
Section: Resultsmentioning
confidence: 99%
“…In this multicenter study Erekson et al (page 333) evaluated the records of 18,576 women from the Nurses' Health Study who reported symptoms of incontinence and linked this information to Medicare utilization data. 5 Only 16% of those reporting incontinence had an identifiable outpatient visit to address incontinence symptoms in the 2 years prior to the survey. It makes sense that incontinence severity was associated with a higher likelihood of a clinic visit as was urgency compared to stress incontinence.…”
Section: Outpatient Visits For Urinary Incontinence In Older Womenmentioning
confidence: 99%
“…UI is infrequently addressed during routine healthcare visits despite its high prevalence and associated symptoms, 7–9 and adverse impact on health and quality of life 10,11 . As a result, UI can impose a significant burden on patients' health and finances 12 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 UI affects over 60% of women in the United States with prevalence estimates varying based upon study population and UI measurement. 5,6 UI is infrequently addressed during routine healthcare visits despite its high prevalence and associated symptoms, [7][8][9] and adverse impact on health and quality of life. 10,11 As a result, UI can impose a significant burden on patients' health and finances.…”
Section: Introductionmentioning
confidence: 99%